Highly Flexible and Efficient Fabric-Based Organic Light-Emitting Devices for Clothing-Shaped Wearable Displays - Seungyeop Choi (Nature Portfolio, 2017)
Abstract Recently, the role of clothing has evolved from merely body protection, maintaining the body temperature, and fashion, to advanced functions such as various types of information delivery, communication, and even augmented reality. With a wireless internet connection, the integration of circuits and sensors, and a portable power supply, clothes become a novel electronic device. Currently, the information display is the most intuitive interface using visualized communication methods and the simultaneous concurrent processing of inputs and outputs between a wearer and functional clothes. The important aspect in this case is to maintain the characteristic softness of the fabrics even when electronic devices are added to the flexible clothes. Silicone-based light-emitting diode (LED) jackets, shirts, and stage costumes have started to appear, but the intrinsic stiffness of inorganic semiconductors causes wearers to feel discomfort; thus, it is difficult to use such devices for everyday purposes. To address this problem, a method of fabricating a thin and flexible emitting fabric utilizing organic light-emitting diodes (OLEDs) was developed in this work. Its flexibility was evaluated, and an analysis of its mechanical bending characteristics and tests of its long-term reliability were carried out.